ANALISIS HUKUM PIDANA TERHADAP TINDAK PIDANA PERDAGANGAN ORANG MELALUI JALUR KEIMIGRASIAN STUDI DI KANTOR IMIGRASI KELAS II TPI BELAWAN - Taufiq, Achmad; Lubis, Junaidi; Indrayani, Leni; Maria, Juliya (Universitas Stikubank, 2026)
Organized cross-border crimes that deprive human rights, namely the Crime of Trafficking in Persons (TPPO), often use population migration routes as the main entry route. This research seeks to review how criminal law is applied to trafficking perpetrators who take advantage of immigration access, as well as uncover the obstacles that arise when law enforcement is carried out in the area of the Class II Immigration Office of TPI Belawan. This study adopts an empirical juridical approach with a qualitative analysis framework. Information collection was carried out through the review of regulatory documents and in-depth discussions with officials at the Class II Immigration Office of TPI Belawan. The research findings indicate that enforcement efforts against trafficking cases in the Belawan operational area rely on Law No. 21 of 2007 concerning the Eradication of Trafficking and Law No. 6 of 2011 concerning Immigration. It was identified that the modes of violation that often occur are falsification of travel documents and the abuse of residence permits to facilitate the sending of illegal migrant workers abroad. Significant obstacles faced include challenges in proving criminal elements, disconnection of the perpetrator network, and lack of synergy between law enforcement agencies in the port area. In closing, improving immigration surveillance capabilities and strengthening partnerships are important means to reduce the threat of human trafficking through the sea route in the Belawan area.